UMA ESCOLA QUE SE TORNOU IGREJA: O METODISMO BOLIVIANO DIANTE DOS DESAFIOS DA URBANIDADE - Okada, Jorge Esteban Wills (2014)
Bolivian society is marked by the overt presence of ethnic cultural strata of indigenous origin. As a consequence of the colonial past,it is still assumed that status of peasant means belonging to an indigenous ethnic group. In this sociocultural reality the Evangelical Methodist Church in Bolivia (IEMB), since its implementation in the early 20th century, gained legitimacy and space in Bolivian society because of their contributions to society with their works of service (education, health, rural development). Currently the IEMB is configured as a rural church, and the Bolivian population is predominantly urban. So urbanity is the challenge for ecclesial and pastoral action, if the IEMB intends to maintain its relevance in Bolivian society. Attempts are made in this research, to point toward in the Wesleyan theological tradition ecclesial foundation for a relevant ecclesial and pastoral presence in the particularities of the Bolivian urban reality